OTORITAS REGISTER KEAGAMAAN DALAM TUTURAN KYAI DAN SANTRI: KAJIAN SOSIOLINGUISTIK - Alin Nadziroh M.S; Emilia Dias C; Salsabilla Is’adiyah Lena; Ingghar Ghupti Nadia Kusmiaji (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
This study examines the authority of religious registers in the speech of Kyai and Santri in the Assalafiy Al-Ikhlas Islamic boarding school environment as a sociolinguistic phenomenon that reflects hierarchical social relations. The research focuses on how registers are used in religious interactions, the forms of registers that emerge, the types of registers used, and the functions of language contained in the speech of Kyai and the responses of Santri. This study aims to explain the meaning of registers, identify forms of religious registers, classify types of registers into closed registers and open registers, and analyse the functions of registers in the context of pesantren communication. The method used is descriptive qualitative with data collection techniques in the form of listening and recording the Kyai's speech obtained through interviews with Santri. The data were analysed through the stages of data reduction, data presentation, and meaning extraction. The results of the study show that religious registers in the Kyai's speech cover the areas of sharia, manners, morals, religious knowledge, and mental development. The registers used are dominated by open registers and have the main functions of conveying religious teachings, character building, reinforcing authority, and maintaining social relations between the Kyai and the Santri